2004
DOI: 10.1152/ajpendo.00372.2003
|View full text |Cite
|
Sign up to set email alerts
|

Glucose deprivation enhances targeting of GLUT1 to lipid rafts in 3T3-L1 adipocytes

Abstract: . Glucose deprivation enhances targeting of GLUT1 to lipid rafts in 3T3-L1 adipocytes. Am J Physiol Endocrinol Metab 286: E568-E576, 2004. First published December 9, 2003 10.1152/ajpendo.00372.2003.-Glucose deprivation dramatically increases glucose transport activity in 3T3-L1 adipocytes without changing the concentration of GLUT1 in the plasma membrane (PM). Recent data suggest that subcompartments within the PM, specifically lipid rafts, may sequester selected proteins and alter their activity. To evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 59 publications
(49 reference statements)
2
35
0
Order By: Relevance
“…SCP-2) cholesterol binding proteins preferentially donate or extract cholesterol from cholesterol-rich, but not cholesterol-poor, microdomains (26,27,136,137,172). The microdomain/lipid raft concept, despite controversy in details, provides a framework for biologists studying localization and function of membrane protein receptors, transporters, and downstream signaling molecules that regulate uptake of cholesterol (86,87,, fatty acids (240)(241)(242), glucose (243)(244)(245)(246)(247)(248)(249)(250)(251)(252)(253)(254), and other activities (216,(255)(256)(257)(258)(259)(260). Cholesterol-poor microdomain preferring cholesterol analogs: BODIPY-coprostanol analog 3; BODIPY-cholesterol analog LZ110a; 22-NBD-cholesterol.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…SCP-2) cholesterol binding proteins preferentially donate or extract cholesterol from cholesterol-rich, but not cholesterol-poor, microdomains (26,27,136,137,172). The microdomain/lipid raft concept, despite controversy in details, provides a framework for biologists studying localization and function of membrane protein receptors, transporters, and downstream signaling molecules that regulate uptake of cholesterol (86,87,, fatty acids (240)(241)(242), glucose (243)(244)(245)(246)(247)(248)(249)(250)(251)(252)(253)(254), and other activities (216,(255)(256)(257)(258)(259)(260). Cholesterol-poor microdomain preferring cholesterol analogs: BODIPY-coprostanol analog 3; BODIPY-cholesterol analog LZ110a; 22-NBD-cholesterol.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Even in the case that similar levels of both glucose transporters are present at both ages, other phenomena may explain the increment in glucose transport observed in older animals. In this respect, Kumar et al (2004) have shown that the composition of the plasma membrane, particularly the lipid rafts, plays an important role in glucose transporter activities, and Sweeney et al (1999) have demonstrated that specific signal transduction pathways may also regulate the activity of the glucose transporters present at the plasma membrane. Alternatively, other mechanisms, such as those regulating the translation of GLUT mRNAs or others, involved in the translocation of glucose transporters to the membrane may also participate 20-day-old Sertoli cells in the increase of glucose uptake with age.…”
Section: Discussionmentioning
confidence: 99%
“…Stomatin is known to associate with glut1, 47 decreasing its affinity for glucose 8 or targeting glut1 to lipid rafts on glucose deprivation. 48 Previously, we hypothesized that the loss of stomatin in these leaky, energy-depleted erythrocytes occurred to allow maximum glucose transport. 3 We have studied the loss of stomatin in OHSt and sdCHC erythroblasts during erythropoiesis to make a direct comparison between the 2 cell types.…”
Section: Stomatin Lossmentioning
confidence: 99%